A Case of Painful Growing Abdominal Wall Mass during Pregnancy Requiring Resection in the Second Trimester - Shlomo M. Stemmer; Cintia Gomes; Elyce H. Cardonick (Case Reports in Obstetrics and Gynecology)
Desmoid fibromatosis (DF) is a rare and locally aggressive neoplasm. We present a case of a 28-year-old previously healthy multigravida who noticed a lump in her abdomen near the umbilicus two months before becoming pregnant. It underwent rapid growth during pregnancy, causing pain and discomfort. Targeted ultrasound of the area showed an irregular mass measuring 0.9×1.7×1.4 cm. The origin of the mass was unclear, suggesting a connection with the intra-abdominal contents. An MRI done three weeks later revealed a subcutaneous ovoid mass measuring 3.0×2.3×3.0 cm, which was significantly larger. Due to pain and rapid growth, surgical resection was done at 25 weeks of pregnancy. Histopathological examination revealed a desmoid tumor. The patient had an uneventful recovery and term vaginal delivery without complications. Hence, our case serves as evidence that DF tumors can be surgically managed during pregnancy with minimal to no complications.